2000
DOI: 10.1093/alcalc/35.6.601
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Alcohol-Related Mortality in Sweden

Abstract: The main aim of the present study was to estimate total alcohol-related mortality in Sweden. For natural deaths, a meta-analysis carried out in Australia was updated to the end of March 1998, and pooled estimates of the relative risks were calculated for different diseases based on data from scientific studies that have been published in the international literature. The proportion of current alcohol drinkers from recent Swedish surveys, and the pooled relative risk estimates were used to estimate disease-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 51 publications
0
33
0
2
Order By: Relevance
“…Bosnar [50] reported significantly high blood alcohol concentrations in suicide cases that occurred with firearms in time of war. Alcohol has been found in 62% of homicide cases in Sweden [51] and 68.6% of murder cases in Norway. [52] According to literature, in the current study, substances were identified at very low rates in the toxicological analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Bosnar [50] reported significantly high blood alcohol concentrations in suicide cases that occurred with firearms in time of war. Alcohol has been found in 62% of homicide cases in Sweden [51] and 68.6% of murder cases in Norway. [52] According to literature, in the current study, substances were identified at very low rates in the toxicological analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis on the relationship between coronary heart disease (CHD) and ethanol intake suggests 20% to 30% reduction in the incidents of CHD. Sjögren et al [37] quantified ethanol-related mortality in Sweden between 1992 and 1996 and found that, in men, ethanol caused 4% of deaths and prevented 5.8%, and in women, 1.4% deaths and 4.6% prevented. Overall, ethanol prevented 1.8% deaths in men and 3.2% in women.…”
Section: Management Recommendationsmentioning
confidence: 99%
“…But if the conditions in Table 2 are examined as well as cardiovascular disease, are benefits to be expected? Sjö rgren et al [24] quantified the alcohol-related mortality in Sweden between the years 1992 and 1996. The results for all natural and unnatural deaths are given in Table 3.…”
Section: The Meta-analyses On the Relationship Between Stroke And Alcmentioning
confidence: 99%